PENERAPAN MODEL KOOPERATIF TIPE STAD BERMEDIA KARTU ALAM PADA PEMBELAJARAN PIPS UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI KENAMPAKAN ALAM DAN RAGAM SOSIAL BUDAYA - Nusahid, Sylvia Rahayu; Kurnia, Dadang; Panjaitan, Regina Lichteria (Jurnal Pena Ilmiah, 2017)
Social Studies is a subject in elementary school, aimed at developing the social skills of elementary school students. Social skills that must be owned by each individual is the interaction. Learning model that emphasizes the interaction and used in this research is STAD cooperative learning model (Student Teams - Achievement Divisions) by using Nature Card Media. This research method is classroom action research by using Model Kemmis and Taggart. This research was conducted in two cycles. the goal is to improve the process and the results of learning results of research on the cycle I and cycle II, student learning outcomes improved very well. The result of the research on the first cycle is 90% which is equivalent to 27 students completed, while the second cycle of 100% is obtained equal to 30 students equipped with 97% target. Thus, the STAD cooperative model by using the Natural Card is declared successful in improving the fourth grade student learning outcomes in the view of Natural and Social and Cultural Variety materials.